Pengaruh Talent Management, Work Life Balance dan Persepsi Dukungan Organisasi Terhadap Retensi Karyawan PT. Supralita Mandiri - Pradhani, Fadilla Ihza Rachma; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study explores how talent management, work–life balance, and employees’ perceptions of organisational support relate to staff retention within PT. Supralita Mandiri. The aim is to determine whether these three aspects, when considered together, significantly shape retention outcomes. Employing a total population sampling approach, the research engaged all 150 employees as respondents. Information was gathered through a Likert-scale questionnaire, and the responses were processed via multiple regression analysis using IBM SPSS 26.0. The analysis demonstrates that talent management exerts a statistically significant but negative influence on retention, indicated by a p-value of 0.012 (below the 0.05 threshold) and a t-statistic of -2.553, which falls short of the critical value of 1.976. Work–life balance similarly shows a negative and significant relationship, with a p-value of 0.000 and a t-score of -3.877. Perceived organisational support also displays a negative, significant effect, with a p-value of 0.001 and a t-score of -3.323. Furthermore, the overall F-test yields a statistic of 18.269, exceeding the critical F-value of 2.43, and a p-value of 0.000, confirming that—when considered simultaneously—talent management, work–life balance, and perceived organisational support collectively exert a substantial impact on the company’s ability to retain employees. Keywords: Talent Management, Work Life Balance, Perceived Organizational Support, Employee Retention